Seasonal wetlands in the Pacific coast of Costa Rica and Nicaragua: environmental characterisation and conservation status - Sasa Marín, Mahmood (2015)
On the Pacific coast of Nicaragua and Costa Rica, rainfall patterns and clay-rich soils allow the development of extensive wetlands. These environments constitute unique habitats for the maintenance of aquatic biodiversity and provide significant ecological services to the surrounding seasonal dry forest. Despite these benefits, wetlands have been severely reduced in the last four decades, and little information is available on their biology and current conservation status. Here, we describe the main limnological traits of 30 sites representing different types of wetlands from four distinct physiographic regions: Tempisque River Lower Basin; Tempisque RiverMiddle Basin; Delta del Estero Real River; and the Oriental Region of Nicaragua. At each site, samples were taken at the beginning (infilling phase), middle (maximum flooded areas) and end (desiccation phase) of the 2010 hydrological cycle. We analysed a set of water parameters (depth, temperature, pH, conductivity, dissolved oxygen, major ions and nutrient concentrations) and biological parameters (shoreline vegetation, chlorophyll a, macrophyte cover) and assessed the conservation status of wetlands using the Index of the State of Conservation of Shallow Lentic Ecosystems (ECELS). In most sites, the water was relatively clear with near basic pH-values, low conductivity, and low levels of dissolved oxygen, nitrates, nitrites, phosphates and sulphates. Chlorophyll a and alkalinity varied through the season and among regions. Ion concentrations were generally low in most wetlands except for those close to estuarine and marine coastal areas. A total of 49 taxa of aquatic plants were found in the study sites, the most common being the emergent Typha domingensis and Thalia geniculata, and the floating Pistia stratiotes and Eichhornia crassipes. Wetlands within the same region exhibited great similarity in their aquatic plant communities but not necessarily in their physicochemical attributes. According to the ECELS index, wetlands could be ranked from medium to good quality, although most of them are threatened by anthropogenic impacts, including those protected at Delta del Estero Real Nature Reserve (Nicaragua) and Palo Verde National Park (Costa Rica).